The Medieval cave village of Casalrotto (Mottola, Apulia): New data on the settlement and its necropolis from archaeological and geophysical measurements. (November 2018) - Di Giacomo, G.; De Giorgi, L.; Ditaranto, I.; Leucci, G.; Miccoli, I.; Scardozzi, G.
Highlights: Upgrading and increment of the knowledge of the Medieval village of Casalrotto. New digital archaeological map. Overview of the dynamics of the site organization and evolution in the centuries. Geophysical data allowing a better definition of the necropolis boundaries. Abstract: This study concerns the main results of the research activity aimed at a new integrated knowledge of Casalrotto, a Medieval cave village (12th–13th century) near Mottola (Province of Taranto southern Italy). The research was based on archaeological and geophysical surveys performed in 2015. In particular, archaeological investigations have allowed the upgrading of the existing plan of the village through Differential Global Position System (DGPS) topographical surveys, while geophysical measurements, using ground-penetrating radar (GPR) and magnetometry in gradiometry configuration, have allowed a better delimitation of the necropolis and the detection of buried structures.